Pengaruh Knowledge Sharing dan Learning Organization terhadap Innovative Work Behavior pada Staf Fakultas USN Kolaka - Agus Ambarsari; Ismanto; Agus Zul Bay (Jurnal Ekonomi dan Bisnis Digital, 2022)
This research aims to determine: The influence of knowledge sharing and learning organization on innovative work behavior among USN Kolaka Faculty Staff. This research is a quantitative research model. Data collection used literature studies, distributing questionnaires and interviews. The population in this study was all USN Kolaka Faculty Staff, totaling 71. The sample size was determined using a saturated sample. Research instrument testing uses validity and reliability tests with SPSS 22.0. The data analysis technique used in this research is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) using the Smart-PLS 4.0 application. Based on the research results, it shows that knowledge sharing has a positive and significant effect on innovative work behavior as indicated by the original sample value of 0.539, t-statistic of 4.522 and p-value of 0.000. and learning organization has a positive and significant effect on innovative work behavior as shown by the original sample value of 0.262, t-statistic of 1.813 and p-value of 0.035.